Role Of Judicial Activism In Environmentaldispute Resolution Before The State Administrative Court - Masyitoh, Andriyani (Universitas Islam Indonesia, 2021)
This study examined the role of judicial activism role in resolving environmental disputes at PTUN. It provided understanding for the judges in order to create justice for both justice seeker and the environment. In this study, the writer used a statutory approach, case study approach, and conceptual approach. Furthermore, the basic concept of judicial activism role and the characteristic of the environmental dispute solution were used as the object of the research. The result revealed that the role of judicial activism role not only strives for just dispute resolution but also keep its environmental justice. Moreover, judges’ decisions is reflected on the principle of preventive action, the precautionary principle, the polluter pays principle. The solution of environmental dispute system condimsidered by the judge panel will excavate ecological's values system.Keywords: Judicial activism; dispute resolution; environmental; PTUNPeran Judicial Activism Dalam Penyelesaian Sengketa Lingkungan Hidup Di Depan Pengadilan Tata Usaha NegaraAbstrakPenelitian ini mengkaji tentang peran judicial activism dalam menyelesaikan sengketa lingkungan di PTUN. Hal ini memberikan pemahaman bagi para hakim untuk menciptakan keadilan bagi pencari keadilan dan lingkungan. Dalam penelitian ini, penulis menggunakan pendekatan undang-undang, pendekatan studi kasus, dan pendekatan konseptual. Selanjutnya, konsep dasar peran judicial activism dan karakteristik penyelesaian sengketa lingkungan digunakan sebagai objek penelitian. Hasil penelitian mengungkapkan bahwa peran judisial activism tidak hanya mengupayakan penyelesaian sengketa yang adil tetapi juga menjaga keadilan lingkungannya. Apalagi putusan hakim tercermin pada prinsip tindakan preventif, prinsip kehati-hatian, prinsip pencemar membayar. Penyelesaian sistem sengketa lingkungan yang dinilai majelis hakim akan menggali sistem nilai ekologis.Kata kunci: Judicial activism; penyelesaian sengketa; lingkungan; PTUN